Initiatives based on local resources − new challenges of agricultural law - Szymańska, Małgorzata (Przegląd Prawa Rolnego, 2018)
The model of sustainable rural development recognises the necessity of local development based on local resources. Investing in the growth of social capital refers to the postulates of implementing an integrated model of rural development, where different local actors engage and cooperate for the common good. Agricultural law also faces these challenges. The social capital of rural areas is characterised by bottom-up activities, locality and territoriality of initiatives, an integrated approach, a partnership action through local action groups, innovation in problem solving, independent management and financing of activities. It encourages local communities to work together to change their surroundings, solve urgent problems, invest in activities diversifying their income, for example through small entrepreneurship, setting up non-agricultural activities, thematic villages, care farms, production of traditional, regional and ecological high quality products, folk handicrafts, crafts.